Green Technology Adoption and Sustainability Initiatives of SMEs in South Africa: The Mediating Role of Knowledge Sharing with Regulatory Support as a Moderator - Khutso Pitso Mankgele (Research Synergy Foundation, 2025)
This study examines the impact of green technology adoption (GTA) on sustainability initiatives, focusing on energy management, water conservation, and waste management within small and medium-sized enterprises (SMEs) in South Africa. The study explores the mediating role of knowledge sharing in enhancing the adoption of green technologies and the moderating effect of regulatory support. A quantitative research design was employed, with a survey administered to 450 participants from SMEs across South Africa. Data were analyzed using SmartPLS, a structural equation modeling tool, to assess the relationships among GTA, sustainability practices, knowledge sharing, and regulatory support. The results indicate that knowledge sharing significantly mediates the relationship between GTA and sustainability initiatives, particularly in the areas of energy management, water conservation, and waste management. Additionally, regulatory support moderated the effect of knowledge sharing on green technology adoption, strengthening the adoption process and amplifying sustainability outcomes. These findings highlight the importance of fostering knowledge-sharing practices within SMEs and the critical role of supportive regulatory frameworks in promoting green technologies. This study contributes to the understanding of how SMEs in South Africa can leverage internal collaboration and external policies to enhance sustainability initiatives, offering valuable insights for policymakers, business leaders, and researchers focused on sustainable development in resource-constrained environments.